Prop-2-en-1-yl 4-(4,5-diphenyl-1H-imidazol-2-yl)benzoate - Shaaban K. Mohamed (Acta Crystallographica Section E, 2013)
The title compound, C25H20N2O2, crystallized with two molecules in the asymmetric unit, in one of which the atoms of the terminal propenyl group are disordered over two sets of sites, with a refined occupancy ratio of 0.870 (4):0.130 (4). The central imidazole ring makes dihedral angles of 25.51 (11), 40.73 (11) and 27.36 (11)° with the three pendant rings in one molecule and 22.56 (10), 60.72 (10) and 5.85 (10)° in the other. In the crystal, molecules are linked by N—H...N and C—H...O hydrogen bonds, forming a three-dimensional network. The crystal structure also features C—H...π interactions and π–π stacking [centroid–centroid distances = 3.8834 (18) and 3.9621 (17) Å] interactions.